An electrochemical immunosensor modified with titanium IV oxide/polyacrylonitrile nanofibers for the determination of a carcinoembryonic antigen. (9th March 2021) - Aslan, Sema
Abstract : A highly sensitive electrochemical carcinoembryonic antigen immunosensor based on TiO2 np/polyacrylonitrile nanofibers electrospun on the surface of the discharged battery coal electrode. Abstract : Carcinoembryonic antigen (CEA) is considerably addressed for the clinical diagnosis of miscellaneous tumor types. In this study, an electrochemical immunosensor for the determination of the CEA biomarker was presented. Titanium(iv ) oxide nanoparticle (TiO2 np)-loaded polyacrylonitrile nanofibers (PANnf) were prepared by electrospinning at the surface of the discharged battery coal electrode (DBC), and loaded with CEA antibodies (Anti-CEA) as the CEA biomarker receptor. Finally, DBC/PANnf + TiO2 np/Anti-CEA was utilized for the CEA detection. Fabrication steps were characterized by cyclic voltammetry and electrochemical impedance spectroscopy in the presence of a [Fe(CN)6 ] 3−/4− probe. Results demonstrated that PANnf and TiO2 nps exhibited a very fine network for immunosensing. The usage of this composite system is a novel immunosensor development approach for the label-free detection of CEA. Under optimal conditions, the DBC/PANnf + TiO2 np/Anti-CEA immunosensor exhibited high sensitivity toward the CEA biomarker in the low concentration range of 0.01–10 ng mL −1, with the detection limit of 0.01 ng mL −1 and relative standard deviation of 1.17 ( n = 5). Results indicated that even very small changes in the CEA concentration can be sensed with the presented system. Also, the recovery of the immunosensor was found to be 99.42% ± 1.41 in real sera samples containing dopamine and ascorbic acid. It has great potential in the clinical screening of divergent cancer biomarkers.